2022
DOI: 10.1097/md.0000000000029920
|View full text |Cite
|
Sign up to set email alerts
|

Neurological symptoms and signs associated with COVID-19 in pediatric patients: a single-center experience

Abstract: There is insufficient evidence on SARS-CoV-2 induced neurological effects. Studies on CNS involvement during COVID-19 in children are limited. This study aims to identify and manage the neurological signs and symptoms in COVID-19-infected pediatric patients during follow up and plan future follow-ups.Children diagnosed COVID-19 and hospitalized in the pediatric pandemic services, between March 18, 2020, and June 18, 2021, were included in the study. Children with underlying neurological disease were excluded f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…Interestingly, the mentioned study showed, for the first time, the presence of SARS-CoV-2 in the brain tissue of a child with MIS-C and acute encephalopathy [ 34 ]. Additionally, patients with neurological manifestations had a significantly higher RBC count and hemoglobin level than patients without neurological manifestations ( p = 0.02 and p = 0.049, respectively), which is in agreement with the findings in another study on the neurological symptoms and signs associated with pediatric COVID-19 [ 35 ]. However, further studies are needed to confirm, explain, and correlate these findings with pediatric COVID-19-related neurological manifestations.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, the mentioned study showed, for the first time, the presence of SARS-CoV-2 in the brain tissue of a child with MIS-C and acute encephalopathy [ 34 ]. Additionally, patients with neurological manifestations had a significantly higher RBC count and hemoglobin level than patients without neurological manifestations ( p = 0.02 and p = 0.049, respectively), which is in agreement with the findings in another study on the neurological symptoms and signs associated with pediatric COVID-19 [ 35 ]. However, further studies are needed to confirm, explain, and correlate these findings with pediatric COVID-19-related neurological manifestations.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the frequency of test-based hyposmia in children with acute SARS-CoV-2 infection was 11.1 %, which is significantly lower than that in most other studies. A possible explanation is that in almost all studies, the frequency of hyposmia (varying from 1.9-86.1 %) was assessed only by questionnaires [1][2][3][4][5][6][7][8]. Only three stud- This document was downloaded for personal use only.…”
Section: Hyposmia In Children With Acute Sars-cov-2 and Other Utrismentioning
confidence: 99%
“…In children, olfactory disturbances are commonly reported in the context of SARS-CoV-2 infection, but the prevalence varies considerably from 1.9 % to 86.1 % [1][2][3][4][5][6][7][8]. This variance could be because the assessment of olfactory dysfunction was mostly based on questionnaires.…”
Section: Introductionmentioning
confidence: 99%
“…According to studies, neurological symptoms appear in more than 35% of COVID-19 patients; in some patients, developing neurological manifestations are their rst symptoms. It is also well documented that SARS-CoV-2 has produced multiple changes in cerebrospinal uid (CSF) content, including increases in white blood cell counts and proteins [5]. A virus enters the CNS via the olfactory nerve, via retrograde transmission through other cranial or peripheral nerves (like the trigeminal nerve, which contains nociceptive cells in the nasal cavity or the vagus nerve), via lymphatic spread or through the choroid plexus, or by hematogenous spread [6].…”
Section: Introductionmentioning
confidence: 99%